Zimbabwe land question, no to white farmer compensation - Mafa, Kwanisai Mafa (Modern Ghana, 2019)
The former colonisers robbed our parents, looted our cattle, displaced our parents, exploited our mineral resources and overused our fertile lands from 1890 to 2000. They unjustly enriched themselves with over ninety years of colonialism, subjugation and crimes against humanity. Zimbabwe was supposed to get restitution from white Rhodesians upon attainment of independence. The struggle for independence was based on land, a compromise was reached which would allow white farmers to continue occupying land and allow a system of willing buyer and willing seller, 2 % of the white population owned 70% of the arable land.